Prevalence of Iron Deficiency Anemia among Adolescent Girls in the City of Saravan - Omid Sabet Ghadam ,; Mohammad Fararouei ,; Mansour Shahraki ,; Zahra Sohrabi, (Journal of Pharmacy and Nutrition Sciences, 2020)
Background and Objective: Iron deficiency anemia (IDA) is the most common type of micronutrient deficiency in the world. Numerous reports indicated that adolescence is a period which has an increased risk of development of IDA. Given the importance of IDA and lack of studies in Saravan, a city of Iran, this study was performed to assess the prevalence of IDA among adolescent girls. Methods: In this cross-sectional study, 460 high-school girls were randomly selected. Demographic data was collected using a questionnaire. Knowledge, attitude and practice of participants with regard to iron deficiency anemia was measured at the beginning of the interview. Accordingly, five cc of blood sample was drawn from each student to determine the prevalence of anemia, which was defined by a hemoglobin level lower than 12 mg / dL. The level of ferritin was analyzed to confirm the IDA for students diagnosed with anemia. Ferritin level lower than 12 ?g / dl was considered as IDA. Data was analyzed using SPSS software version 22. Results: Prevalence of anemia and IDA was 24% (n = 111) and 12.6% (n = 58), respectively. Results showed that 37 % of students had good knowledge, 45. 5 % good attitude, and 6.7 % had good practice. Also, there was no significant association between IDA and socio-economic status including parental education, job, and household income (P>0.05). Conclusion: The findings of this study showed that the prevalence of IDA was moderate in Saravan city. Given the importance of IDA and its complications, further studies are needed, especially in high risk populations for IDA such as children.